Exploring the job satisfaction and occupational commitment in Fire and Rescue Department in Ipoh, Perak - Mohd Saini, Nur Haryatie; Omar, Siti Aida (2007)
Fire & Rescue Department in Malaysia as a whole are still improving their quality in terms on delivering their services towards the society. Fire & Rescue Department in Malaysia was established in 1883 in Selangor which their new vision is Towards World Class Fire & Rescue Organization” in order to parallel with our country vision which is ‘Vision 2020’. This study is to exploring the job Satisfaction and occupational commitment among firemen in Fire and Rescue Department in Ipoh, Perak. A cluster random sampling of 75 firemen was giving the questionnaire on 2 major issues. The first issue is to examine the level of job satisfaction towards their job. Second issue is regarding the occupational commitment among firemen while doing their task given. Job satisfaction and occupational commitment dimensions were hypothesized to positively related. Result generally supported the hypotheses. We also hypothesized that job satisfaction and firemen’s position whereby both variables has positively related among each other.